Determination of time of death based on basic histological stain and immunostain changes - Ezlan Elias; Khairul Osman; Sharifa Abdul Aziz; Abdul Halim Mansar; Siti Fatimah Ibrahim; Jamaludin Mohamed (penerbit ukm, 2004)
Establishing time of death has been extensively studied for the last 30 years. Parameters that have been studied included body temperature, biochemistry of rigor mortis, putrefactive changes and entomology. Despite an extensive study in these parameters it was found that all of the parameters were very much dependent on external factors like changes in surrounding temperature and activities done prior to death. To solve this problem, we decided to monitor the mechanism that occurs during death. Until now, various researches have found that during the early stage of death, heart and perfusion to the cells will stop. This will cause the cells to start the death process. The death of the cell will occurs either through apoptosis or necrosis. During apoptosis the cells will switch on and off a few proteins in a sequence. Based on this understanding, a study was conducted to determine if area ratio of apoptosis: necrosis and apoptotic p53 and Bcl-2 markers can be used as a reliable postmortem interval marker (PMI). Sampling of the study had involved 100 dead human skins with a known PMI. All samples were obtained from forensic unit of Hospital Kuala Lumpur (UFHKL). Ratio of apoptosis: necrosis areas were determined using hematoxilin and eosin staining while apoptosis p53 and Bcl-2 markers were done using an apoptosis kit. All staining were then indexed and plotted against PMI data obtained from UFHKL. Results indicated that there were no significant correlations between ratio of apoptosis: necrosis area against PMI (p = 0.144). Whereas for both apoptotic markers p53 and Bcl-2 PMI had shown a significant correlation (p < 0.000 for both results). In conclusion, we suggest that p53 and Bcl-2 parameters should be studied further since it is very likely that it could be a good indicator for PMI.